PENGARUH MODEL PEMBELAJARAN MATEMATIKA CREATIVE PROBLEM SOLVING (CPS) BERBANTUAN CD INTERAKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA SISWA SMA KELAS X - Asikin, Moh; Pujiadi, - (Lembaran Ilmu Kependidikan, 2008)
This research is aimed to find out whether students’ activity in learning processwith CPS model assisted with interactive CD positively influences their problemsolving ability. Secondly, it is aimed to find whether or not the problem solving abilityof students joining this program is better than those joining the conventional one.Thirdly, the study is aimed to know whether there is a difference in the problemsolving ability among upper, middle, and lower students. This research is a trueexperimental research. Research variable consists of students’ activity (independentvariable) and students’ problem solving ability (dependent variable). The measuringinstruments used were students’ activity observation sheets and problem solving tests.The data were analyzed by the use of regression analysis, independent sample t test,and comparison of means of one way anova. The results of the research show thatstudents’ activity in learning with CPS model assisted with interactive CD has positiveinfluence on their problem solving ability, problem solving ability of the studentsjoining the model is better than those joining the conventional one, and there is adifference of problem solving ability among upper, middle, and lower group studentsin the learning.Kata Kunci: Problem Solving, CPS, CD Interaktif, Pemecahan Masalah, Kreatif